Cost per care of the first year of direct antiviral agents in the Liguria Region: a multicenter analysis - Cenderello G; Fanizza C; Marenco S; Nicolini LA; Artioli S; Baldissarro I; Dentone C; De Leo P; Di Biagio A (Dove Medical Press, 2017)
Giovanni Cenderello,1 Caterina Fanizza,2 Simona Marenco,3 Laura Ambra Nicolini,4 Stefania Artioli,5 Isabella Baldissarro,3 Chiara Dentone,6 Pasqualina De Leo,7 Antonio Di Biagio4 1SC Malattie Infettive, EO Ospedali Galliera, 2Rete ligure HIV, 3SSD Epatologia, AOU S. Martino, 4Clinica Malattie Infettive, AOU S. Martino, Genoa, 5SC Malattie Infettive ASL5 La Spezia, 6SC Malattie Infettive, ASL‑1, Sanremo, 7SC Malattie Infettive ASL2, San Paolo, Savona, Italy Aims: Despite the remarkable efficacy shown in clinical practice, concerns have been raised about the costs associated with direct antiviral agent (DAA) therapy. This article presents the real-life costs for DAA treatment sustained by the Italian National Health Service in the Liguria Region (Northern Italy).Methods: A retrospective analysis of the cost per care sustained for DAA treatment, relating to the period from January 1 to December 31, 2015 in five centers in Liguria was performed. All patients undergoing DAA-based treatments for hepatitis C virus (HCV) infection were enrolled. On-treatment costs included: HCV treatment, laboratory test, outpatient services, attended visits, drugs used for the management of adverse events (erythropoietin, albumin or red blood cell packs) and inpatient service admissions.Results: In total, 327 patients were enrolled. No difference in terms of sustained virologic response (SVR) rate among different treatments was reported. The majority (85.0%) of patients did not report any side effects and only 15 (4.6%) required hospital admission. Forty-two patients (12.8%) required high-cost drugs for the management of adverse events. The overall cost sustained was €14,744,433. DAA±ribavirin (RBV) accounted for the wide majority of this cost (98.9%; €14,585,123). Genotype (GT) 1, the most commonly treated GT, was associated with an average cost of €43,445 per patient. Detailed analysis of the costs for GT 1 showed the treatment based on ritonavir boosted paritaprevir/ombitasvir + dasabuvir±RBV with an average cost of €24,978 (RBV+) and €25,448 (RBV−) per patient was the most cost-effective. The average cost per SVR was €48,184. Once again, the ritonavir boosted paritaprevir/ombitasvir + dasabuvir regimen was associated with the lowest cost/SVR (€25,448/SVR [GT 1b] and similar results for other GTs).Conclusion: Antiviral regimen is the major contributor to costs in the treatment of HCV infection. Appropriate regimen selection could result in a major cost saving, which can be reinvested to allow more patients to be treated. Keywords: HCV treatment, HCV costs, cost efficacy